Research of Manual and Automated Testing - Valatkevičius, Vytaras; Šešok, Dmitrij (Jaunųjų mokslininkų darbai, 2018)
This article provides two methods for manual and automated testing effort assessment. Using these methods, the influence on time and cost of manual and automated testing was compared. A study with a real, developed project has revealed that in the long run, automated tests help reduce the time and cost of the testing process.